Equine viral arteritis : epidemiological and intervention perspectives (2010)
ABSTRACT: Equine viral arteritis is an infectious viral disease of horses that causes serious economic losses due to the presentation of abortions, respiratory disease and loss of performance. After the initial infection males can become persistently infected carriers scattering infection through semen, a situation that brings indirect economic losses by restrictions on international trade of horses and semen from breeding and from countries at risk of infection with the virus. Outbreaks of infection have been reported in several American countries with which Colombia has active links of import and export of horses and semen. This article focuses on creating awareness of the key points of infection and on examples of how infection has been distributed in countries that have developed horse breeding, such as Argentina, a country aware of the origin and distribution of the infection. This study will help us understand how to assess, prevent and/ or control the entry of such a devastating infection for the equine industry.